Evaluation of the accumulation of organochlorine pesticides (ocps) in Bostrychus sinensis fish growing the soai rap estuary - Ho Chi Minh city - Tong, Nguyen Xuan; Huong, Tran Thi Thu; Huong, Mai; Thuy, Duong Thi; Luc, Huynh Cong (Academia Journal of Biology, 2019)
This study was conducted from May to November 2017 to evaluate the accumulation of organochlorine pesticide chemicals (OCPs) in Bostrychus sinensis fish growing at the Soai Rap estuary, Ho Chi Minh City, Vietnam. The pesticide chemicals in the tissues of fish and the sediments of the estuary were analyzed using a gas chromatography method and Varian GC-450 (ECD) instrument. The results showed that in all tissue samples of fish, the content of DDTs was the highest (9.524 ng/g), followed by Aldrin (1.209 ng/g); HCHs (1.972 ng/g); Dieldrin (1.743 ng/g) and Endosunfans (1.053 ng/g), and the lowest values were Heptachlor (0.807 ng/g) and Eldrin (0.715 ng/g). The content of OCPs in all sediment samples from the study area was found to be lower than Vietnamese standard 43: 2012 /MONRE and some other standards in the world. The bioaccumulation factor of OCPs in the tissue of fish was very low level (BAF < 100), for DDTs at low levels (100 < BAF < 500). The Biota-Sediment Accumulation Factor (BSAF) of the seven substances in the sediment was Dieldrin > DDTs > Aldrin > HCHs > Endosunfans > Heptachlor > Endrin.